2009
DOI: 10.1007/s00438-009-0498-7
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and structure of the linear mitochondrial genome of Pneumocystis carinii

Abstract: With the exception of a few genes, most of the mitochondrial (mt) genome of Pneumocystis carinii has not previously been sequenced. Shotgun sequences generated as a result of the Pneumocystis Genome Project (PGP) were assembled with the gap4 assembly program into a 23-kb contig. Annotation of the mt genome identified 4 open reading frames and 20 tRNAs in addition to 17 other genes: ATP synthase, subunits 6, 8, and 9; cytochrome c oxidase, subunits 1, 2, and 3; NADH dehydrogenase, subunits 1, 2, 3, 4, 4L, 5, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
4
16
0
Order By: Relevance
“…Nonetheless, we could not rule out the staining of mitochondrial DNA by the dye. As mitochondrial DNA is small (23 kb, [29]), its relative contribution to nuclear fluorescence intensity remains negligible. Moreover, computer-aided three-dimensional reconstruction showed that a unique mitochondrion is present in the studied life cycle parasite stages [30], [31], thus keeping the ratio mitochondrial-to-nuclear DNA content to one in these forms.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we could not rule out the staining of mitochondrial DNA by the dye. As mitochondrial DNA is small (23 kb, [29]), its relative contribution to nuclear fluorescence intensity remains negligible. Moreover, computer-aided three-dimensional reconstruction showed that a unique mitochondrion is present in the studied life cycle parasite stages [30], [31], thus keeping the ratio mitochondrial-to-nuclear DNA content to one in these forms.…”
Section: Discussionmentioning
confidence: 99%
“…PCR products ranged from 252 to 333 bp (nested PCR at the mtLSU rRNA gene) and from 334 to 480 bp (nested PCR at the mtSSU rRNA gene). The sequences under analysis are part of the ribosome and are coded by the mitochondrial genome, and no introns were detected in the mitochondrial genome (82). Direct sequencing of PCR products revealed that each Pneumocystis mtLSU rDNA or mtSSU rDNA sequence could be associated with a unique bat species (Tables 9 and 10; Fig.…”
Section: Detection Ofmentioning
confidence: 99%
“…Because of the low DNA purity, the assembly necessitated an innovative approach using iterative identification of the fungal homologies among the reads from the host and lung microbiota. The genome sequences of the mitochondria were also obtained from the same sequencings, as well as by PCR [4], [5].…”
Section: Genome Sequencesmentioning
confidence: 99%
“…The data of the mitochondrial genomes are from Sesterhenn et al [4] and Ma et al [5].bThe nuclear assemblies of the three species are considered to be incomplete and do not include repetitive elements.cThe numbers for P. jirovecii and P. carinii overestimate proteome size because some peptides are from incomplete coding DNA sequences at ends of contigs.dOnly complete copies in P. carinii assembly were considered.…”
Section: Genomic Assembliesmentioning
confidence: 99%